Citrus sinensis and Vitis vinifera Protect Cardiomyocytes from Doxorubicin-Induced Oxidative Stress: Evaluation of Onconutraceutical Potential of Vegetable Smoothies - Giacomo Pepe; Emanuela Salviati; Shara Francesca Rapa; Carmine Ostacolo; Stella Cascioferro; Michele Manfra; Giuseppina Autore; Stefania Marzocco; Pietro Campiglia (MDPI AG, 2020)
The interest towards nutraceuticals able to counteract drug side effects is continuously growing in current chemotherapeutic protocols. In the present study, we demonstrated that smoothies containing mixtures of Citrus sinensis and Vitis vinifera L. cv. Aglianico N, two typical fruits of the Mediterranean diet, possess bioactive polyphenols that protect cardiomyocytes against doxorubicin-induced oxidative stress. The polyphenolic extracts isolated from Citrus sinensis- and Vitis vinifera-based functional smoothies were deeply characterized by Liquid Chromatography-Mass Spectrometry methods. Subsequently, the functional smoothies and relative mixtures were tested to verify their ability to affect cellular viability and oxidative stress parameters in embryonic cardiomyocyte cells (H9c2), and human breast adenocarcinoma cell line (MCF-7) exposed to doxorubicin. Interestingly, we found that the mix resulting from Citrus sinensis and Vitis vinifera association in ratio 1:1 was able to reduce cardiomyocytes damage induced by anthracyclines, without significantly interfering with the pro-apoptotic activity of the drug on breast cancer cells. These results point out the potential use of vegetable smoothies as adjuvants functional foods for chemotherapeutic anticancer protocols.